2014
DOI: 10.1007/s10450-014-9619-7
|View full text |Cite
|
Sign up to set email alerts
|

Numerical study of flow maldistribution and depressurization strategies in a small-scale axial adsorber

Abstract: Flow maldistribution and local high velocity in an axial adsorber is numerically studied to investigate the potential occurrence of sorbent pulverization and uneven utility. A considerable maldistribution induced by the entrance effect and local high velocity caused by rapid gas discharge during depressurization is observed. Three types of gas distributors and different depressurization strategies are then proposed and studied to determine their capabilities to create uniform velocity profiles. Results show th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 16 publications
1
5
0
Order By: Relevance
“…The governing equations are consistent with previous research [27,28], and the simulation results were verified experimentally by use of the product of the O 2 concentration on the axial flow adsorber [28].…”
Section: Governing Equationssupporting
confidence: 82%
See 3 more Smart Citations
“…The governing equations are consistent with previous research [27,28], and the simulation results were verified experimentally by use of the product of the O 2 concentration on the axial flow adsorber [28].…”
Section: Governing Equationssupporting
confidence: 82%
“…It can be seen that the four radial-flow adsorbers give similar patterns of pressure changes with the order of the value of CF-π>CF-Z>CP-Z>CP-π, indicating that the effect of the flow type on the pressure change in the bed during the radial-flow PSA process is small. In order to compare the gas distribution of the adsorber in the PSA oxygen generator, a maldistribution factor integrating the surface and corresponding velocity, Mf, was introduced as in [27,36].…”
Section: Modeling Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…It is very effective to study gas separation by numerical simulation [22][23][24][25][26]. However, most of the studies are based on the 1-D or 2-D RFA [27], and few studies have been reported in research of PSA oxygen production based on 3-D RFA. In actual PSA processes, the gas separation in the adsorption bed is a coupling process of multiple complicated processes such as gas flow, heat transfer and mass transfer.…”
Section: Introductionmentioning
confidence: 99%